Methods of Assessing Feasibility of Involvement of the Audit Organization in the Public Procurement - EFREMOVA, Elena I.; FEDCHENKO, Elena A.; KURASHOVA, Anna A.; SHEVEREVA, Elena A.; BONDARCHUK, Natalya V.; LASHCHINSKAYA, Natalia V. (Journal of Advanced Research in Law and Economics; Vol 10 No 8 (2019): JARLE Volume X Issue 8(46) Winter 2019DO - 10.14505/jarle.v10.8(46).11, 2019)
The legislation of the Russian Federation provides for General principles and criteria establishing rules for the selection of performers that meet such requirements as ensuring healthy competition, efficient use of budget funds, openness and transparency of public procurement procedures. All principles and criteria are applicable to the determination of the order of participation of audit organizations; however, separate or additional conditions are not provided by the legislation on public procurement. Selection of participation of audit organizations is carried out on the General principles with the indication of special criteria determined by customers in the relevant documentation for participation in public procurement.